The Conceptual Design of An Electro-Magnetic Power Generator - Azahari, Faiq Taquiddin; Atel, Maxmillain Newman Anak; Samsuri, Siti Salwa; Abdul Aziz, Azunaidi (Semesta Teknika, 2023)
Nowadays, magnetic field induction is a dependable renewable energy source that can convert magnetic fields into electrical power. In this study, our objective is to propose a low-cost free energy generator design based on neodymium. The main problems with existing generators were air pollution, noise pollution, and even fuel price volatility. To begin addressing this issue, we compared 6 currently used generators. We concentrated on 5 criteria in light of this outcome. Our top considerations in this study are cost and maintenance. Then comes the size, weight, and noise. The best electromagnetic power generators for satisfying all the criterion domains are determined using Pugh's matrix. It demonstrates that electromagnetic power generators have a high score of 95 compared to natural gas, portable, and diesel power generators. We have also calculated the resulting voltage from the selected number of permanent magnet coils. This calculation shows 60V resulting in 9600 turns. As a result, we draw the conclusion that the reduction of problems like noise and air pollution makes this power generator look like a very appealing alternative.